Property and the law in energy and natural resources - McHarg, Aileen (Oxford : Oxford University Press, 2010)
Examining the multiple interfaces between property law and energy and natural resources law, this text deals with perennial questions about the ownership of energy and natural resources as well as dealing with the role of property rights in environmental regulation and the property rights of indigenous communities.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Property; Natural resources -- Law and legislation; Energy development -- Law and legislation; Right of property